A Preliminary Study on the Relationship Between High-Resolution Computed Tomography and Pulmonary Function in People at Risk of Developing Chronic Obstructive Pulmonary Disease - Lv, Rui; Xie, Mengyao; Jin, Huaqian; Shu, Pingping; Ouyang, Mingli; Wang, Yanmao; Yao, Dan; Yang, Lehe; Huang, Xiaoying; Wang, Yiran (Frontiers in Medicine, 2022)
Objectives: Patients with chronic obstructive pulmonary disease (COPD) have high morbidity and mortality, the opportunity to carry out a thoracic high-resolution CT (HRCT) scan may increase the possibility to identify the group at risk of disease.The aim of our study was to explore the differences in HRCT emphysema parameters, air trapping parameters, and lung density parameters between high and low-risk patients of COPD and evaluate their correlation with lung function indicators. Methods: In this retrospective, single-center cohort study, we enrolled outpatients from the Physical Examination Center and Respiratory Medicine of The First Affiliated Hospital of Wenzhou Medical University. The patients who were ≥40 years-old, had chronic cough or sputum production, and/or had exposure to risk factors for the disease and had not reached the diagnostic criteria is considered people at risk of COPD. They are divided into low-risk group and high-risk group according to FEV1/FVC≥80% and 80%>FEV1/FVC≥70%. Data on clinical characteristics, clinical symptom score, lung function, and HRCT were recorded. Results: 72 COPD high-risk patients and 86 COPD low-risk patients were enrolled in the study, and the air trapping index of left, right, and bilateral lungs of the high-risk group were higher than those of the low-risk group. However, the result of mean expiratory lung density was opposite. The emphysema index of left, right, and bilateral lungs were negatively correlated with FEV1/FVC (correlation coefficients were -0.33, -0.22, -0.26). Consistently, the air trapping index of left and right lungs and bilateral lungs were negatively correlated with FEV1/FVC(correlation coefficients were -0.33, -0.23, -0.28). Additionally, the mean expiratory lung density of left and right lungs and bilateral lungs were positively correlated with FEV1/FVC (correlation coefficients were 0.31, 0.25, 0.29). Conclusion: The emphysema index, air trapping index and the mean expiratory lung density shows significantly positive correlation with FEV1/FVC which can be used to assess the pulmonary function status of people at risk of COPD and provide a useful supplement for the early and comprehensive assessment of the disease.